Co-pyrolysis of wheat husk and residual tyre: Techno-economic analysis, performance and emission characteristics of pyro oil in a diesel engine. (September 2022) - Rajkumar, P.; Murugavelh, Somasundaram
Abstract: The Wheat husk and the residual tyre were thermochemically converted to fuel in a single stage fixed bed reactor. The elemental analysis of the wheat husk and residual tyre indicated higher volatile matter. The higher heating value of residual tyre was 36.20 MJ/kg. The thermogravimetric study indicated the temperature of co-pyrolysis as 500 °C. Pyro oil yield was studied for 1:0, 1:1, 2:1, 1:2, 0:1 blends of wheat husk and residual tyre. Gas chromatography and Fourier transform Infrared spectroscopy indicated the presence of aromatic compounds in the pyro oil. The wheat husk – residual tyre pyro oil's kinematic viscosity was 3.8 cSt. Co-pyrolysis produces fuel with higher energy content. The maximum brake thermal efficiency of the wheat husk - residual tyre pyrolysis oil is 29.4 %. Carbon monoxide emission from the blended fuel was 0.12 %. The cost of pyro oil was ₹ 32.50/L Residual tyre has been effectively converted into fuel. Graphical abstract: Unlabelled Image Highlights: Residual tyre a hazardous material is converted into fuel through pyrolysis. Co-pyrolysis reported 58.5 wt% of pyro oil. GC–MS reported more petroleum based compounds. The gross energy content of pyro oil was 36.20 MJ /kg. The brake thermal efficiency of pyro oil was 29.4 %.